Bond Behavior of Wet-Bonded Carbon Fiber-Reinforced Polymer-Concrete Interface Subjected to Moisture - Yiyan Lu; Tao Zhu; Shan Li; Zhenzhen Liu (International Journal of Polymer Science)
The use of carbon fiber-reinforced polymer (CFRP) composite materials to strengthen concrete structures has become popular in coastal regions with high humidity levels. However, many concrete structures in these places remain wet as a result of tides and wave-splashing, so they cannot be completely dried before repair. Therefore, it is vital to investigate the effects of moisture on the initial and long-term bond behavior between CFRP and wet concrete. This research assesses the effects of moisture (i) during CFRP application and (ii) throughout the service life. Before CFRP bonding, the concrete blocks are preconditioned with a water content of 4.73% (termed “wet-bonding”). Three different epoxy resins are applied to study the bond performance of the CFRP-concrete interface when subjected to moisture (95% relative humidity). A total of 45 double-lap shear specimens were tested at the beginning of exposure and again after 1, 3, 6, and 12 months. All specimens with normal epoxy resins exhibited adhesive failure. The failure mode of specimens with hydrophobic epoxy resin changed from cohesive failure to mixed cohesive/adhesive failure and to adhesive failure according to the duration of exposure. Under moisture conditioning, the maximum shear stress (τmax) and corresponding slip (smax) of the bond-slip curve first increased and then decreased or fluctuated over time. The same tendency was seen in the ultimate strain transmitted to the CFRP sheet, the interfacial fracture energy (Gf), and the ultimate load (Pu). Analytical models of Gf and Pu for the CFRP-concrete interface under moisture conditioning are presented.